A Federated Architecture for Enhancing Security and Scalability in IoT-Cloud Integrated Systems - Zangana, Hewa; Yazdeen , Abdulmajeed (PT. SNN MEDIA TECH PRESS, 2025)
The exponential growth of the Internet of Things (IoT) and its integration with cloud computing has introduced significant challenges related to security, scalability, and data privacy. This paper proposes a novel federated architecture that leverages federated learning and distributed security mechanisms to enhance the resilience and scalability of IoT-cloud integrated systems. By decentralizing data processing and security enforcement, the architecture mitigates common attack vectors such as centralized point-of-failure, data leakage, and unauthorized access. The proposed system is designed with modular security components including lightweight encryption, dynamic trust management, and blockchain-inspired audit trails. A performance evaluation conducted through simulated environments and real-world IoT testbeds demonstrates improved latency, resource efficiency, and defense against cyber threats when compared to conventional centralized systems. This research contributes to the advancement of secure and scalable IoT-cloud infrastructures and offers a viable path for industrial and smart city deployments.